Alternative Legal Solutions for Petty Theft Cases - Wahyudi; Gunawan Widjaja (Bulletin of Community Engagement, 2024)
This kind of approach focuses on rehabilitation and taking responsibility for one’s action rather than severe punishment. Pretrial interventions also allow the offender to participate in rehabilitative programs aimed at skills training and preventing future offenses without the stressful effect of the traditional criminal scion. More training and resources for police are crucial in the management of petty theft cases without the loss of public trust in the system of justice. Wanting community education efforts are also important in the elimination of petty theft. The study in this research uses the literature research method. Literature research method, also known as literature study, is an approach in research that relies on secondary data through the collection, analysis, and interpretation of published materials relevant to the research topic. The rationale for alternative legal solutions for petty theft cases cases demonstrates an advancement of criminal justice systems going beyond punitive measures. With the help of the restorative methods of justice, the two parties- the offender and the victim – become participants in the process of redress, which makes it possible for the offender to accept responsibility for his/her behaviour and for the victim to be reinstated with a sense of justice.